Profiling of 1-aminocyclopropane-1-carboxylic acid and selected phytohormones in Arabidopsis using liquid chromatography-tandem mass spectrometry - Karady, Michal; Hladík, Pavel; Cermanová, Kateřina; Jiroutová, Petra; Antoniadi, Ioanna; Casanova-Sáez, Rubén; Ljung, Karin; Novák, Ondřej (Plant methods, 2024)
BACKGROUND: Gaseous phytohormone ethylene levels are directly influenced by the production of its immediate non-volatile precursor 1-aminocyclopropane-1-carboxylic acid (ACC). Owing to the strongly acidic character of the ACC molecule, its quantification has been difficult to perform. Here, we present a simple and straightforward validated method for accurate quantification of not only ACC levels, but also major members of other important phytohormonal classes - auxins, cytokinins, jasmonic acid, abscisic acid and salicylic acid from the same biological sample. RESULTS: The presented technique facilitates the analysis of 15 compounds by liquid chromatography coupled with tandem mass spectrometry. It was optimized and validated for 10 mg of fresh weight plant material. The extraction procedure is composed of a minimal amount of necessary steps. Accuracy and precision were the basis for evaluating the method, together with process efficiency, recovery and matrix effects as validation parameters. The examined compounds comprise important groups of phytohormones, their active forms and some of their metabolites, including six cytokinins, four auxins, two jasmonates, abscisic acid, salicylic acid and 1-aminocyclopropane-1-carboxylic acid. The resulting method was used to examine their contents in selected Arabidopsis thaliana mutant lines. CONCLUSION: This profiling method enables a very straightforward approach for indirect ethylene study and explores how it interacts, based on content levels, with other phytohormonal groups in plants.
Keywords: Jasmonic acid; Abscisic acid; Ethylene; ACC; Plant hormones; 1-aminocyclopropane-1-carboxylic acid; Salicylic acid; Mass spectrometry; Liquid chromatography; Arabidopsis; Cytokinin; Auxin